Carbon dots from Artemisiae Argyi Folium Carbonisata: strengthening the anti-frostbite ability. Issue 1 (1st January 2021) - Kong, Hui; Zhao, Yusheng; Zhu, Yafan; Xiong, Wei; Luo, Juan; Cheng, Jinjun; Zhang, Yue; Zhang, Meiling; Qu, Huihua; Zhao, Yan
Abstract: In this study, novel carbon dots (CDs) were discovered and separated from Artemisiae Argyi Folium Carbonisata (AAFC) aqueous extract. AAFC-CDs were characterised by a series of methods, mainly including electron microscopy, optical technology and X-ray photoelectron spectroscopy (XPS). Results displayed that AAFC-CDs with a quantum yield (QY) around 0.19% had a size distribution between 6.0 and 10.0 nm and possessed a nearly spherical shape, with a lattice spacing of 0.369 nm. In mice, AAFC-CDs reduced the tissue damage, ear frostbite, and body stiffness caused by cold, and provided energy by increasing the use of blood glucose. The mechanism may be by decreasing concentration of IL-1βk, TNF-α and reducing the rise in blood glucose levels caused by frostbite. This study is the first to indicate that CDs may be the active constituent of AAFC against frostbite, suggesting their potential for clinical applications.